TVET Learning Innovation on Automotive Virtual Laboratory Based on Cloud Openstack - Dede; Abdullah, Ade Ghafar; Mulyanti, Budi; Rohendi, Dedi; Sulaeman (Journal of Technical Education and Training, 2020)
Changes and industrial transformation globally in the era of the industrial revolution 4.0 resulted in technological gaps between the industrial and academic environment, especially in the field of vocational education in automotive engineering. The purpose of this research is to design a virtual laboratory network model that contains the latest material sources from the industry called Virtual Cloud Automotive Laboratory (VCAL). The cloud network model in virtual laboratories is designed such as the Infrastructure as a Services (IaaS) platform, the Platform as a Services (PaaS), Software as a Services (SaaS). The design process is carried out by the PPDIO method, namely Prepare, Plan, Design, Implement, Operate, and Optimize. VCAL is built using open stack software consisting of a database and user interface. The SaaS platform enables industries to share competency and occupational materials for maintenance and repair of light vehicle or automotive engines in the form of 3D view web, video, audio-visual that can be accessed by students, lecturers in enriching aspects of repair and maintenance skills. The test results are limited to Automotive Cloud Virtual Laboratory access done by 10 users simultaneously with different devices, namely PC computers, notebooks, Android smartphones, the results show that the server used can run very well.